Morphological variability in some persian clover (Trifolium resupinatum L.) populations from Ordu province (Turkey) - Onal Asci O.; Kasko Arici Y.; Nalbanto F.; Deveci M.; Acar Z. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
The characterization of native populations is of extreme importance for the identification of elite genotypes to be considered for breeding programs. For that reason, the objective of this study was to determine the variability of some morphological characteristics of 15 local Persian clover (Trifolium resupinatum L.) populations from the 5 coastal counties of Ordu (Turkey). These populations were classified according to plant height, crown diameter, stem diameter, number of stems/plant, leaflet length, leaflet width and dry weight. For this purpose, data were analyzed by Principal Component Analysis (PCA) and Hierarchical Cluster analysis (HCA). According to HCA, the local populations of Persian clover were grouped in 4 clusters and resulted similar in rates ranging from 54.11% to 90.46%.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)